Design and Installation of Street Light for Public Lighting Business in Industrial 4.0 - Firman Yudianto; Rizqi Putri Nourma Budiarti; Zainatul Mufarikkoh (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2019)
Industry development 4.0 makes every company always make continuous innovation so that it can provide satisfaction to each of its customers. In addition, it can increase the improvement in income obtained from the company. The aesthetics of the location of the company and the appearance of industrial sites will be able to attract customers to be able to increase the ordering of these industrial products. Calculation and installation of public street lighting around the location of the industry will be able to provide customer interest to come and be able to provide benefits to the company's production. The design and the installation of public street lighting will provide solutions for business feasibility in increasing revenue in the industrial era 4.0 by increasing financial and economic aspects.